2013
DOI: 10.3109/00207454.2013.866951
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effects profile of levetiracetam in epilepsy: a more detailed look

Abstract: The adverse effects profile of levetiracetam in epilepsy is still being fully described. We recently published a Cochrane Review evaluating the effectiveness of levetiracetam, added on to usual care, in treating drug-resistant focal epilepsy. The five most common adverse effects were reported and analysed with no scope for reporting any less common adverse effects than those. Here, we report and analyse the remaining adverse effects (including the five most common). These were (in decreasing order of frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 20 publications
2
49
0
2
Order By: Relevance
“…Sleep disturbances so far have been reported only occasionally [21,25] and probably are not in the focus of physicians' attention. In the regulatory monotherapy trial, however, insomnia was reported by patients treated with levetiracetam more than twice as often as by patients on CR carbamazepine [26].…”
Section: Discussionmentioning
confidence: 93%
“…Sleep disturbances so far have been reported only occasionally [21,25] and probably are not in the focus of physicians' attention. In the regulatory monotherapy trial, however, insomnia was reported by patients treated with levetiracetam more than twice as often as by patients on CR carbamazepine [26].…”
Section: Discussionmentioning
confidence: 93%
“…Even though previous clinical observations suggested an increased risk of upper respiratory infections with levetiracetam , our subanalysis failed to show a specific effect on these infections, thus suggesting that this facilitating effect concerns all infectious disease and is not specific of any particular infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…These effects may increase the risk of developing infectious diseases and some clinical data suggest a higher frequency of upper respiratory infectious diseases in subjects under treatment with specific drugs .…”
Section: Introductionmentioning
confidence: 99%
“…24,1015 In a systematic review of ten randomised controlled trials by Mbizvo et al, adverse effect profile of LEV in patients of drug-resistant epilepsy was studied, and rash due to LEV was reported in only two studies. It was noted that only symptoms affecting more than 5 or 10% of participants of the groups were published in these ten trials 16. In the study by Cheung et al, out of 55 patients of cADR due to various AEDs identified over 16.5 years, there was only one patient with rashes due to LEV, though one of the reasons maybe that being a newly introduced AED it may not have been prescribed much in the initial few years 17.…”
Section: Discussionmentioning
confidence: 99%